Using Linear Filters to Process VLF-EM Data - A Case Study From the Wasa a Kropong-Gyapa Area (Journal of Science and Technology, 2016)
The processing and subsequent interpretation of VLF-EM data are enhanced by the application of linear filters to the observed in-phase component of the vertical magnetic field coming from sub-surface conductors. An anomaly in the in-phase component exhibits a crossover exposure.The filter process involves mathematically passing the shape of an expected anomaly signature along the various traverses. When this anomaly outline matches one in the measured data, a large positive number is obtained whose position along the traverse coincides with a conductive zone within the ground. Noise in the measured data, reverse crossovers and anomalies due to deep-seated conductors are all suppressed mathematically.By adjusting the filter polarity, one can selectively filter the data for a measured anomaly response. All the filtered values are plotted on the traverses and the values are contoured to produce a map, which can be correlated with the geological map of the area to show the trend of subsurface conductors.Linear filters of FRASER [1] and KAROUS-HJELT [2], have been applied consistently to the VLF-EM data collected in different directions along thirteen traverses between Wassa Akropong and Gyapa in the Western Region of Ghana. The results of the study show that some of the positions of the subsurface conductors located by the filtering process coincide with areas of known gold mineralization.